2018
DOI: 10.1007/s00381-018-3954-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of image-guided stereotactic hypofractionated radiation therapy as adjuvant treatment of craniopharyngiomas. A review

Abstract: Image-guided radiosurgery holds the dose distributions and precision of frame-based techniques with the remarkable advantage of multiple-session treatments that are better tolerated by sensitive peritumoral structures, such as the optic pathway and hypothalamus. This, together with the comfort of a frameless technique, candidates frameless image-guided radiosurgery to be the first option for the adjuvant post-operative treatment of craniopharyngiomas in children and young adults when total resection cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Image-guided technology is also a vital method for skull base surgery, as this anatomic region is deep and narrow, and contains critical structures 51 . For example, the cavernous sinus is surrounded by cranial nerves, including the abducens nerve, the oculomotor nerve, the trochlear nerve, and the third, fourth, and sixth divisions of trigeminal nerves 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image-guided technology is also a vital method for skull base surgery, as this anatomic region is deep and narrow, and contains critical structures 51 . For example, the cavernous sinus is surrounded by cranial nerves, including the abducens nerve, the oculomotor nerve, the trochlear nerve, and the third, fourth, and sixth divisions of trigeminal nerves 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of stereotaxy is that it is difficult to reach millimeter-level positional accuracy 62 . For lesions deep in the brain, for example, craniopharyngiomas (adjacent to the hypothalamus, pituitary, optic nerve, and important vessels), and the risk of using this technology is high 51 . In recent years, frameless technology (e.g., landmarks) and robotics have come to be used in neurosurgery 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Puataweepong et al, who administered CyberKnife treatment to 100 consecutive patients with tumors proximal to the optic nerve, reported that the incidence of visual dysfunction was 0 [22]. Conti et al, who investigated damage to the hypothalamus, reported that the incidence of hypothalamic disorder after treatment was insignificant even after long-term observation [23]. Moreover, Yang et al investigated prognosis with the extent of resection taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy, although beneficial in reducing tumor recurrence, is controversial due to the potential neurovascular morbidity. Post-operative conventional radiotherapy (CRT) for CP is associated with new pituitary deficits, including worsening of partial hypopituitarism, observed in 20-60% of irradiated patients studied in the literature, and radiation induced optic neuropathy [14,15]. In contrast, fractionated stereotactic radiation therapy (FSRT) and stereotactic radiosurgery (SRS) have lower toxicity rates and greater safety and efficacy in terms of hypothalamic and visual function.…”
Section: Current Managementmentioning
confidence: 99%